2018
DOI: 10.1089/mdr.2017.0407
|View full text |Cite
|
Sign up to set email alerts
|

Distinctiveness and Similarities Between Extended-Spectrum β-Lactamase-Producing Escherichia coli Isolated from Cattle and the Community in Israel

Abstract: The goal of this study was to compare the molecular features of bovine- and human community-acquired extended-spectrum β-lactamase (ESBL)-producing Escherichia coli in Israel. Bovine ESBL-producing E. coli were isolated during a point-prevalence study from the main farming locations throughout Israel. Human ESBL-producing E. coli isolates were collected from community-acquired urinary tract infection cases. Molecular typing was done initially by repetitive extragenic palindromic-PCR. Representative isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Recent cut-offs advocate that clonal relatedness is accepted for the K. pneumoniae isolates when allele difference are less than 10 (Schürch et al, 2018); using this cutoff we could assume that there is no genetic link between the horse and human isolates. Despite that, other authors have interpreted these cutoffs from a different perspective as they advocate that 16 to 21 allele differences between isolates from carriers from different species suggest that transmission has occurred (Adler et al, 2017; Lifshitz et al, 2018). Moreover, most of the few studies that define cutoffs for cgMLST analysis are based on human isolates only (Schürch et al, 2018) and do not take into account interspecies transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Recent cut-offs advocate that clonal relatedness is accepted for the K. pneumoniae isolates when allele difference are less than 10 (Schürch et al, 2018); using this cutoff we could assume that there is no genetic link between the horse and human isolates. Despite that, other authors have interpreted these cutoffs from a different perspective as they advocate that 16 to 21 allele differences between isolates from carriers from different species suggest that transmission has occurred (Adler et al, 2017; Lifshitz et al, 2018). Moreover, most of the few studies that define cutoffs for cgMLST analysis are based on human isolates only (Schürch et al, 2018) and do not take into account interspecies transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, our finding carries public health implications. First, ESBLproducing E. coli lineages found in food-producing animals have also been found in human infections (Carattoli, 2008;Lifshitz et al, 2018). Moreover, the widespread use of β-lactams in dairy cattle may coselect ESBL-producing colistin-resistant strains, increasing the abundance and mobilization of the mcr-1 gene between strains, or even between bacterial species, potentially increasing human exposure to the gene through various pathways (European Medicines Agency, 2013).…”
mentioning
confidence: 99%
“…The cluster analysis of swine E. coli isolates showed that the 25 different ST types can be classified into 3 CCs, namely CC10 [ST10 (7) 5), and TDY2 (1)] and ST48 [JN (1)]. The three ST58 swine E. coli strains derived from TDY2 belonged to the group CC155, while the other two ST410 swine E. coli strains derived from TDY2 belonged to the group CC23 (Supplementary Table 4).…”
Section: Cluster Analysis Of Mlst Genotyping Relationshipmentioning
confidence: 99%